EFEKTIVITAS DAN PERANAN PARTISIPASI PUBLIK DALAM PENYAMPAIAN LAPORAN DUGAAN PELANGGARAN PEMILU DAN PEMILIHAN UNTUK MEWUJUDKAN PEMILU DAN PEMILIHAN YANG DEMOKRATIS - Sutarno (Jurnal Keadilan Pemilu, 2021)
Participatory supervision is a means given to the community for providing direct control over the implementation of elections to realize democratic elections. The effectiveness of the participatory supervision must be measured by certain parameters, one of which is the submission to Bawaslu of reports of alleged election and violation. However, it is necessary to study further the extent to which the effectiveness of participatory supervision can realize democratic elections, particularly in terms of reporting alleged violations to Bawaslu. This paper uses a qualitative research methods by identifying and conducting an understanding of the literature to see the benchmarks for the effectiveness of participatory supervision. The effect of participatory monitoring on the realization of democratic elections has a considerable impact on the development of democracy in Indonesia, due to an increase in public participation during the previous election period, especially in terms of submitting information and reports of election violations. The effect of participatory supervision has also increased public awareness and concern for democratic, integrity, and dignified elections.